دراسة ويبومترية لتقييم وترتيب المواقع الإلكترونية للجامعات الحكومية الليبية على شبكة الإنترنت (Journal of Academic Research, 2019)
The proliferation of websites in various sectors called for the necessity of setting standards and measurements for evaluation and development. The study focused on the field of Web-Metrics and their application on the Libyan governmental universities websites, in order to determine their efficiency and compliance with a set of structural standards that were applied in the study. The study followed the method of content analysis using three specialized websites (WebPageTese, SimilarWeb, Yellow Lab Tools) to analyze the content of university websites, and then use the comparison method to compare results. The study concluded that the sites of most universities were low in the results of the tests used, Also, despite re-testing the sites for a period of five months, their results did not actually change and this indicates that the Libyan universities do not follow their sites, and that the ranking of universities according to their websites differs according to the criteria used in their evaluation. The study notes the importance of using evaluation sites and applications Sites by Libyan public universities to identify weaknesses in their locations and the parts that need to be worked on, developed and improved upon.